2010
DOI: 10.1007/s00380-009-1214-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of pulmonary vein isolation for arrhythmic events in a patient with catecholaminergic polymorphic ventricular tachycardia

Abstract: An 18-year-old woman with catecholaminergic polymorphic ventricular tachycardia (CPVT) underwent pulmonary vein isolation (PVI) because of frequent and inappropriate shocks from an implantable cardioverter defibrillator (ICD) associated with atrial fibrillation (AF) with a rapid ventricular response. While the PVI did not completely suppress the AF induced by an isoproterenol infusion, the Holter monitor recordings demonstrated a major decrease in the clinical episodes of AF and ventricular tachyarrhythmias in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Supraventricular dysrhythmias such as atrial fibrillation and sick sinus syndrome are present in 16-26% of the patients 1,5, 9 and may provoke ventricular arrhythmias in some patients. 13 In young children, supraventricular arrhythmias can precede the occurrence of the classic CPVT phenotype. 14 These supraventricular arrhythmias are hypothesized to arise from dysfunctional calcium handling in atrial cardiomyocytes (comparable to the ventricular phenotype).…”
mentioning
confidence: 99%
“…Supraventricular dysrhythmias such as atrial fibrillation and sick sinus syndrome are present in 16-26% of the patients 1,5, 9 and may provoke ventricular arrhythmias in some patients. 13 In young children, supraventricular arrhythmias can precede the occurrence of the classic CPVT phenotype. 14 These supraventricular arrhythmias are hypothesized to arise from dysfunctional calcium handling in atrial cardiomyocytes (comparable to the ventricular phenotype).…”
mentioning
confidence: 99%
“…13 However, the conclusion that ␤-adrenergic activation and RYR2 phosphorylation do not play a role is at odds with the fact that 3 of the 5 case reports linking AF to CPVT found that AF was induced by exercise or emotional stress. [7][8][9][10][11] Because the CPVT-causing RYR2 mutations identified in the case reports were distinct from those studied by Shan et al, 23 it is conceivable that different CPVT-causing RYR2 mutations induce AF by different mechanisms. Consistent with this possibility, CPVT mice expressing both R176Q-RYR2 via one allele and RYR2 channels lacking the CaMKII phosphorylation site (S2418A-RYR2) via the other allele were resistant to pacing-induced AF.…”
mentioning
confidence: 80%
“…Indeed, many single-gene mutations and some polymorphisms are linked to electric and structural changes in atria that are predicted to promote electric ectopy and reentry. 6 Recent human studies have identified a link between lone AF and mutations of the sarcoplasmic reticulum (SR) Ca 2ϩ release channels (ie, ryanodine receptor 2 [RYR2]), [7][8][9][10][11][12] which, along with mutations in calsequestrin2 (CASQ2), a regulator of RYR2 activity, cause a deadly ventricular arrhythmia called catecholaminergic polymorphic ventricular tachycardia (CPVT). These CPVT mutations of RYR2 and CASQ2 are associated with enhanced RYR2 activity and spontaneous Ca 2ϩ leak from the SR. 13 The link between RYR2 channel mutations and AF is of particular interest because abnormal atrial Ca 2ϩ homeostasis is a hallmark of chronic AF.…”
mentioning
confidence: 99%
“…28,49,50 Indeed, CPVT patients may be at increased risk of inappropriate shocks due to CPVT-related supraventricular arrhythmias. 51,52 In 2008, the first three CPVT patients with successful prevention of adrenergically-mediated arrhythmias with left cardiac sympathic denervation (LCSD) were described, some with long-term follow-up. 53 After this, more successful experiences with LCSD in CPVT have been published.…”
Section: Reviewmentioning
confidence: 99%